BIODIVERSITY DISCLOSURE AND ESG PERFORMANCE: DOES A CHIEF SUSTAINABILITY OFFICER IMPORTANT? - Rizki, Tabah; Perdana, Halim Dedy (EP FEB UNS, 2024)
This study analyzes the impact of corporate biodiversity disclosure (CBD) on ESG performance, with the chief sustainability officer (CSO) as the moderating variable. Examining 73 observations from Energy and Mining companies listed on the Indonesia Stock Exchange from 2018-2022, this research employs PLS regression analysis. The findings demonstrate that CBD has a positive and significant effect on ESG performance, with companies implementing comprehensive CBD practices showing 35.4% higher ESG performance scores and 12.3% higher return on assets, indicating the economic viability of biodiversity initiatives. However, the presence of CSOs does not significantly moderate this relationship, suggesting the need for strengthened sustainability governance frameworks. These findings provide implications for academics, practitioners, and regulators in enhancing both CBD implementation and CSO effectiveness to achieve sustainable development targets while maintaining economic performance.